Problems of creating an effective system of health technology assessment at the early stages of the drug life cycle - Nazarkina, V. M.; Nemchenko, A. S.; Podolsky, I. M.; Babenko, M. M.; Koba, T. M. (Social Pharmacy in Health Care, 2024)
Aim. To study modern approaches to the formation and functioning of the Horizon Scanning (HS) system and early health technology assessment (HTА), in particular, for the treatment of rare diseases with significant unmet medical needs. Materials and methods. The analysis, systematization and synthesis of data from scientific publications, analytical reports, guidelines, information from official websites of regulatory authorities, HTА and HS agencies were used. Results. The analysis of the theoretical foundations and regulatory support for the processes of forming an effective HS system at the early stages of the life cycle has been performed. HS systems, the so-called “early awareness and alert systems”, are aimed at identifying, filtering and prioritizing new and innovative technologies with a significant predicted impact on health, costs, society and the healthcare system in order to inform policy makers, purchasers and healthcare providers or improve early access. The HS system allows for proactive planning and decision-making on the use and reimbursement of new medicines based on preliminary assessments of budgetary impact and clinical efficacy. Conclusions. For the national HTA system, which currently is at the stage of development, it is important to adapt positive international experience in this area and provide functionality for HS, early assessment, early dialogue, managed access with the development of the evidence base. It is advisable to apply the “light” model and join the international cooperation in this area.